1964
DOI: 10.1002/ar.1091500104
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in submandibular and retrolingual glands following parasympathetic denervation in rats

Abstract: Alterations in size and structure of submandibular and retrolingual glands of the rat produced by unilateral sectioning of the chorda tympani, or the lingual nerve, or the glandular branch which leaves the lingual and innervates both glands, are described. The glands were studied 1, 2, 4, 8, 12 and 16 days after nerve section.The weight of the glands increased the first day after nerve section and decreased markedly from then on, reaching 40 to 70% of the initial weight after 16 days. In the glands where the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1966
1966
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…The effect of pilocarpine was found to be quite contrary to that of atropine, since this secretory agent decreased the weight of both the denervated and the contralateral gland to a similar level. These findings suggest that the weight increase after parasympathetic denervation is due to the secretory inactivity in the gland, which is in accordance with previous histological studies [Peronace et al, 1964].…”
Section: Secretory Responsessupporting
confidence: 93%
“…The effect of pilocarpine was found to be quite contrary to that of atropine, since this secretory agent decreased the weight of both the denervated and the contralateral gland to a similar level. These findings suggest that the weight increase after parasympathetic denervation is due to the secretory inactivity in the gland, which is in accordance with previous histological studies [Peronace et al, 1964].…”
Section: Secretory Responsessupporting
confidence: 93%
“…Loss of acinar cells due to any mechanism, such as cell death, would cause a decrease in the AQP5 protein level. Furthermore, previous reports showed that the decrease in the SMG weight occurs during the first week after CTD (5,7,32,49). For this reason, we examined the possibility of the involvement of apoptosis following CTD.…”
Section: Resultsmentioning
confidence: 95%
“…The third effect of CTD on the SMG is a reduction in the gland weight (5,7,32,49). Upon CTD, the gland weight decreases by 50% at the latest by a week after the operation (7,32).…”
Section: Discussionmentioning
confidence: 99%
“…The ultrastructural appearance of the chorda included in the ligation is one of extensive loss of axons and demonstrates the damage that the parasympathetic supply suffers by inclusion of the chorda. Destruction of the chorda is itself followed by glandular atrophy (10)(11)(12)(13), which was reported to be greater in rodents (14).…”
Section: Discussionmentioning
confidence: 99%